Aktuální problematika, tendence a metody česko-maďarského uměleckého překladu - Annamária Péntek; Elizabeth Kőrösová (Acta Universitatis Carolinae: Philologica, 2019)
This study deals with problematic features of Czech-Hungarian translation, focusing primarily on issues regarding translations of contemporary Hungarian literature, not only from the aesthetic point of view but from a linguistic one as well. The study examines possible methods and processes in Czech-Hungarian literary translations published from 2000, highlighting translation solutions for non-standard issues. Within translatological research, various translation solutions are examined, taking into account grammatical and lexical features of the two languages. The study includes a summary of Czech-Hungarian translation difficulties as a practical guide for novice translators. An analysis of frequent mistakes in translating from Hungarian to Czech makes up a portion of this work. The study presents a survey of the problems in translating calques, dialects, and slang. Translation solutions are demonstrated with specific examples from translations of three Hungarian novels: A kőszívű ember fiai by Mór Jókai; Feleségverseny by György Spiró; and A lány, aki nem beszélt by Krisztina Tóth.